2020
DOI: 10.1097/qmh.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Hospital Admission and Discharge Management: An Umbrella Review of Systematic Reviews

Abstract: Background: The aim of this umbrella review was to summarize the research evidence on programs to improve the transition between ambulatory and hospital care. Methods: The MEDLINE database and the Cochrane library were searched. Systematic reviews of randomized controlled trials published between January 2000 and September 2018 in English or German were included. Studies were eligible if an assessment or coordination intervention had been evaluated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Our results are in line with other umbrella reviews investigating interventions to improve hospital admissions and transitional care strategies in adult populations in calling for more robust RCTS that extend beyond the hospital stay and meet the patients’ needs [ 103 , 104 ]. A systematic review investigating the effect of transitional care interventions on hospital readmissions in older medical patients also reported that more RCTs are required that include an intervention with minimum duration of one month and that target high- risk patients [ 105 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our results are in line with other umbrella reviews investigating interventions to improve hospital admissions and transitional care strategies in adult populations in calling for more robust RCTS that extend beyond the hospital stay and meet the patients’ needs [ 103 , 104 ]. A systematic review investigating the effect of transitional care interventions on hospital readmissions in older medical patients also reported that more RCTs are required that include an intervention with minimum duration of one month and that target high- risk patients [ 105 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, we encourage a system-level integration of clinical data to bridge the information gap between each transition. The more clinical data available, the more prediction models can be practically useful for efficiency and quality improvement in home care [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Since LTHC patients were usually at older age with multiple comorbidities, it is challenging to balance between investments in a readmission reduction effort and readmission cost for homecare providers [8,9]. Risk management predictive models allow home care providers to arrange the priority of medical interventions according to the patient's hospitalization risk and optimize the utilization of medical resources [10]. However, there remains a gap in putting predictive models into actual practice for home care patients [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a multitude of studies aiming to improve health care at this interface, yet the evidence is inconclusive. Furthermore, the transition from home to the hospital is not well researched [3][4][5][6]. The VESPEERA programme for hospital admissions and discharges addressed this issue by involving primary care teams in a multifaceted intervention to enhance information transfers across the whole process from admission by the general practice, the hospital stay and discharge up to follow-up care by the general practice.…”
Section: Introductionmentioning
confidence: 99%